Exploring the Role of Digital Literacy and E-Commerce in Shaping Digital Entrepreneurial Interest - Fauziah, Nida; Mubarok, Teten Muhamad Sapril; Maulani, Galih Abdul Fatah (Jurnal Inovasi Bisnis dan Kewirausahaan, 2024)
This study examines the impact of digital literacy and e-commerce experience on students' digital entrepreneurship intention. Digital literacy is important in the digital technology era and e-commerce experience also play a role in shaping the view of the digital business world. This study aims to explore the relationship between digital literacy, e-commerce experience, and students digital entrepreneurial intention. Through this study, it it is expected that the important factors that influence the digital entrepreneurship intention among students will be revealed, as well as the importance of digital understanding in the context of today's business. The population in this study are students at Garut University. This type of research is quantitative research with non-experimental / survey research type. The sample used in this study were 359 respondents who were distributed to respondents using a questionnaire directly and through Google form media then processed using SPSS statistics 26 using simple purposive sampling technique. The analytical tool used in this study is multiple linear regression, data quality test coefficient of determination and hypothesis test. The purpose of this study is to determine whether there is an influence of Digital Literacy and E-commerce on Students Digital Entrepreneurship Interest at Garut University. The results of the study states that the Digital Literacy Variable has a positive and significant effect of 46.7% on Digital Entrepreneurship Interest. The E-commerce Variable has a positive and significant effect of 40.8% on Digital Entrepreneurship Interest. The Digital Literacy and E-commerce Variables have a positive and significant effect of 49.1% on Digital Entrepreneurship Interest. While the remaining 50.9% is influenced by other variables not mentioned in this research model.